2008
DOI: 10.1613/jair.2502
|View full text |Cite
|
Sign up to set email alerts
|

A Multiagent Approach to Autonomous Intersection Management

Abstract: Artificial intelligence research is ushering in a new era of sophisticated, mass-market transportation technology. While computers can already fly a passenger jet better than a trained human pilot, people are still faced with the dangerous yet tedious task of driving automobiles. Intelligent Transportation Systems (ITS) is the field that focuses on integrating information technology with vehicles and transportation infrastructure to make transportation safer, cheaper, and more efficient. Recent advances in ITS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
712
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,089 publications
(727 citation statements)
references
References 32 publications
1
712
0
14
Order By: Relevance
“…Các phương pháp thường được các nhà khoa học nghiên cứu và ứng dụng, đó là giải thuật di truyền [1], [2], lôgic mờ [3], [4] và gần đây nhất là hệ thống đa tác tử [5], [6], [7], [8].…”
Section: Tổng Quan Các Mô Hình đIều Khiển Tín Hiệu đèN Giao Thôngunclassified
See 2 more Smart Citations
“…Các phương pháp thường được các nhà khoa học nghiên cứu và ứng dụng, đó là giải thuật di truyền [1], [2], lôgic mờ [3], [4] và gần đây nhất là hệ thống đa tác tử [5], [6], [7], [8].…”
Section: Tổng Quan Các Mô Hình đIều Khiển Tín Hiệu đèN Giao Thôngunclassified
“…Tiếp cận đa tác tử trong việc điều khiển tín hiệu đèn GT ngày càng được ưa chuộng [5], [6], [7]. Hầu hết các mô hình đều tập trung vào việc phân tích mục tiêu, các nhiệm vụ của các tác tử và cơ chế giao tiếp của chúng.…”
Section: đIều Khiển Tín Hiệu đèN Gt Sử Dụng Hệ Thống đA Tác Tửunclassified
See 1 more Smart Citation
“…In previous work, the estimation of arrival times and arrival velocities is based on a heuristic we called the optimistic/pessimistic heuristic, that derives the arrival time and arrival velocity based on a prediction about whether the vehicle can arrive at the intersection without the intervention of other vehicles [8]. However, this heuristic does not guarantee that the vehicle can arrive at the intersection at the estimated arrival time or the estimated arrival velocity; in fact, our experiments showed that vehicles were often unable to reach the intersection at the correct time, forcing them to cancel their reservations after holding the reservations for quite some time.…”
Section: Preventing Vehicles From Canceling Their Reservationsmentioning
confidence: 99%
“…Navigation functions are practical tools introduced in robotics for solving collision avoidance problems [6] such as formation [7], rendezvous and consensus scenarios. Decentralized navigation functions have two great benefits.…”
Section: Introductionmentioning
confidence: 99%